2017
DOI: 10.1080/10717544.2016.1247924
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of intratracheal inhalation of temozolomide (TMZ) loaded into gold nanoparticles and/or liposomes against urethane-induced lung cancer in BALB/c mice

Abstract: The current study aimed to develop gold nanoparticles (GNPs) and liposome-embedded gold nanoparticles (LGNPs) as drug carriers for temozolomide (TMZ) and investigate the possible therapeutic effects of intratracheal inhalation of nanoformulation of TMZ-loaded gold nanoparticles (TGNPs) and liposome-embedded TGNPs (LTGNPs) against urethane-induced lung cancer in BALB/c mice. Physicochemical characters and zeta potential studies for gold nanoparticles (GNPs) and liposome-embedded gold nanoparticles (LGNPs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Urethane-induced lung cancer has been well-characterized and accepted as a model for human lung adenocarcinoma. In lung cancer research, the urethane model of lung cancer has been widely used, particularly in BALB/c mice (37,38). In the present study, BALB/c wild-type (WT) and BALB/c TRAF1 knockout (TRAF1 KO) mice received 7 consecutive weekly i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Urethane-induced lung cancer has been well-characterized and accepted as a model for human lung adenocarcinoma. In lung cancer research, the urethane model of lung cancer has been widely used, particularly in BALB/c mice (37,38). In the present study, BALB/c wild-type (WT) and BALB/c TRAF1 knockout (TRAF1 KO) mice received 7 consecutive weekly i.p.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this in vivo study showed that both TGNPs and LTGNPs have an improved curative effect and low toxicity, and the synergistic effect produced by LTGNPs can improve the properties of the particles. 117 Alalaiwe et al conducted a test in order to evaluate the quantitative oral bioavailability of PEG-coated GNPs in rats by measuring the concentration of gold in the blood, liver, spleen, and kidneys of rats at different time intervals after oral administration of a certain dose of GNPs; 118 however, this classical approach to analyze bioavailability needs more studies. In recent years, hyperthermia and photodynamic therapy have received considerable attention, and numerous studies have shown their great potential for cancer treatment.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…All these properties, together with easy surface functionalisation, make AuNPs versatile platforms for diagnosis, therapy, drug delivery and tissue engineering. Recently, in order to reduce the risk associated with systemic exposure, the use of inhaled AuNPs as drug carrier and radiosensitiser (Hamzawy et al 2017;Hao et al 2015) has been investigated.…”
Section: Introductionmentioning
confidence: 99%